Consumer preference for certified sustainable palm oil with environmental sustainability attributes: a choice experiment approach - Dauda, Suleiman Alhaji; Sidique, Shaufique Fahmi; Tey, Yeong Sheng; Djama, Marcel (Editorial Universidad de Almería, 2021)
Increasing consumer preference for sustainable palm oil necessitates a paradigm shift towards certified sustainable palm oil (CSPO), and the introduction of CSPO cooking oil, with environmental attribute certification and eco-labelling, will be hallmarks of the necessary sustainability standard. In this study, we applied a choice experiment to investigate supply side consumer preferences, and to estimate willingness to pay (WTP) for cooking oil certified under Roundtable for Sustainable Palm oil (RSPO). Sustainability standards for the palm oil industry were introduced to address environmental issues, such as biodiversity conservation, and the harmful reduction in CO2 emission. To achieve this, we examined Malaysian consumer knowledge of the CSPO, and investigated its influence on their choice of palm oil supply value chain model, considering biodiversity conservation, CO2 reduction and the willingness to pay (WTP). The main finding of this study indicated that Malaysian consumers are willing to pay more than a 5% price premium for RSPO certified palm (cooking) oil, while the most prioritized attributes is the mass balanced supply chain model that included both moderate levels of biodiversity conservation and of CO2 emission.